Visual stimulation with food pictures in the regulation of hunger hormones and nutrient deposition, a potential contributor to the obesity crisis - Duszka, Kalina; Gregor, András; Reichel, Martin Willibald; Baierl, Andreas; Fahrngruber, Christine; König, Jürgen (PLOS ONE, 2020)
Food cues affect hunger and nutritional choices. Omnipresent stimulation with palatable food contributes to the epidemics of obesity. The objective of the study was to investigate the impact of food cues on appetite-related hormones and to assess the functionality of the secreted hormones on macronutrient uptake in healthy subjects. Additionally, we aimed at verifying differences in the response of total and active ghrelin to stimulation with food pictures and to a meal followed by the stimulation. We were also interested in the identification of factors contributing to response to food cues. We recruited healthy, non-obese participants for two independent cross-over studies. During the first study, the subjects were presented random non-food pictures on the first day and pictures of foods on the second day of the study. Throughout the second study, following the picture session, the participants were additionally asked to drink a milkshake. Concentrations of blood glucose, triglycerides and hunger-related hormones were measured. The results showed that concentrations of several hormones measured in the blood are interdependent. In the case of ghrelin and gastric inhibitory peptide (GIP) as well as ghrelin and glucagon-like peptide-1 (GLP-1), this co-occurrence relies on the visual cues. Regulation of total ghrelin concentration following food stimulation is highly individual and responders showed upregulated total ghrelin, while the concentration of active ghrelin decreases following a meal. Protein content and colour intensity of food pictures reversely correlated with participants’ rating of the pictures. We conclude that observation of food pictures influences the concentration of several appetite-related hormones. The close link of visual clues to physiological responses is likely of clinical relevance. Additionally, the protein content of displayed foods and green colour intensity in pictures may serve as a predictor of subjective attractiveness of the presented meal.